Emotional Intelligence as a Determinant of Readiness for Online Learning - Buzdar, Muhammad Ayub; Ali, Akhtar; Tariq, Riaz Ul Haq (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Students’ performance in online learning environments is associated with their readiness to adopt a digital learning approach. Traditional concept of readiness for online learning is connected with students’ competencies of using technology for learning purposes. We in this research, however, investigated psychometric aspects of students’ preparedness for online learning. Purpose of the activity was to examine students’ emotional intelligence as a determinant of their readiness for online learning. 432 learners enrolled in distance learning programs participated in the study. Wong and Law emotional intelligence scale (WLEIS) and online learning readiness scale (OLRS) were adapted to collect the required data. Regression coefficient portrays a large predictive contribution of students’ emotional intelligence in explaining variance in their readiness for e-learning.